E-016 Enterprise stent assisted coil embolization of cerebral aneurysms. (16th November 2010) - Afshani, M; Hoit, D; Morris, S; Barr, J; Arthur, A
Abstract : Introduction: Cerebral aneurysms have morphometric features that influence the initial and long term success of coil embolization. Advances in coil assist technology now permit endovascular treatment of previously uncoilable aneurysms. We report a single institution experience of 52 patients with intracranial aneurysms that necessitated stent adjunctive treatment for occlusion, with angiographic follow-up studies available on 46 of the 52 patients. Methods: Between May 2007 and November 2009, 52 patients with 55 intracranial aneurysms were treated by Enterprise stent mediated coil embolization. Initial and short term demographic, clinical and radiographic outcome data were collected and analyzed for technical success of the initial intervention, clinical complication rates, 6 month occlusion and recannalization rates, and delayed radiographic complications. Results: Seven aneurysms in seven patients were re-treatments of previously coiled aneurysms. 48 aneurysms in 45 patients were stent coiled as an initial treatment. 13 were treated after an acute subarachnoid hemorrhage. Initial procedural results showed complete occlusion (Raymond I) in 14/55 (25%), neck remnant (Raymond II) in 12/55 (22%) and incomplete occlusion (Raymond III) in 29/55(53%). Periprocedural complications were infrequent, with no aneurysm perforations, and one thromboembolic event resulting in an anterior cerebral artery stroke. Stent migration was the most frequent technical complication occurring in four cases. Six month follow-up arteriography was available for 46 patients with 48 aneurysms. Complete occlusion was present in 28/48 (58%) aneurysms, neck remnant or regrowth was present in 12/48 (25%) and 8/48 (17%) were incompletely treated. Five patients with five aneurysms eventually underwent further embolization, and delayed placement of a second enterprise stent was necessary in one patient. In-stent stenosis was an infrequent problem occurring in 4/48 (8%), none of which were hemodynamically significant. One patient developed a mild stenosis in a perforating vessel adjacent to the stent. Conclusion: The Enterprise stent is a safe and useful device in treating wide necked cerebral aneurysms. Our short term experience demonstrates a low rate of complications and a trend toward progressive occlusion among patients who initially had a neck or dome remnant.